Cognitive Beliefs and Their Relationship to Self-Organized Learning Strategies at the Preparatory Stage (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the level of cognitive beliefs, as well as to identify the level of self-organized learning strategies among intermediate school students. The study also aims to identify the differences in the level of self-organized learning strategies among intermediate school students in term of gender, branch (scientific, literary). In order to achieve the research objectives, the researcher designed a scale to measure the cognitive beliefs. As for the scale of self-organized learning strategies, the researcher adopted a scale of (Pintrich et al. 1991), which was translated by (Izzat Abdelhamid, 1999) , For self-organized learning strategies, the sample consisted of (400) students from the research population, which were randomly selected from the preparatory stage / morning study. The results showed that intermediate school students have cognitive beliefs; the level of self-organized learning strategy is statistically significant compared to the cognitive beliefs. Moreover, males are more capable of self-organized learning than females; individuals with scientific disciplines are more capable of self-organized learning strategies compared to human subjects. Finally, there is no statistically significant difference in the interaction between gender and the study specialization at the level of cognitive beliefs.